GAMBARAN TINGKAT PENGETAHUAN PENDERITA HIPERTENSI TENTANG MANAJEMEN HIPERTENSI DI PUSKESMAS II DENPASAR BARAT - Ina Wula Pangabang; Ni Luh Gede Intan Saraswati; AA Istri Dalam Hana Yundari (Rena Cipta Mandiri, 2026)
Hypertension is a non-communicable disease with a high prevalence that increases the risk of heart disease, stroke, and kidney failure. Hypertension control is influenced by patients' ability to manage their condition, which is closely related to their level of knowledge. This study aimed to describe the level of knowledge of patients with hypertension regarding hypertension management in the working area of UPTD Puskesmas II West Denpasar. The study employed a quantitative descriptive design with a cross-sectional approach. A total of 50 respondents were selected using a purposive sampling technique. Data were collected using a questionnaire consisting of 15 questions and analyzed using univariate analysis. The results showed that the majority of respondents were aged 40–50 years (52%), female (58%), had completed senior high school education (42%), and were unemployed (66%). Most respondents demonstrated a good level of knowledge (98%), while 2% had a moderate level of knowledge. It can be concluded that the level of knowledge among patients with hypertension was generally good. Therefore, this should be maintained through continuous health education to support optimal hypertension control.